Application of Rice Straw Compost and NPK Fertilizer to Increase The Growth of Kale Land (Ipomoea reptans poir) - Raksun, Ahmad; Merta, I Wayan; Mertha, Gde (Jurnal Biologi Tropis, 2024)
Kale land can grow well in various environmental conditions. Fertilization is one way that can be done to increase the growth of  Ipomoea reptans poir using both organic and inorganic fertilizers. Research on the application of rice straw compost and NPK fertilizer to increase the size of  stems and leaves of Ipomoea reptans poir has been completed in 2023. This research aims to analyze: (1) the effectiveness of using NPK fertilizer on the size of  stems and leaves of Ipomoea reptans poir, 2) the effectiveness of using rice straw compost on the size of  stems and leaves of Ipomoea reptans poir, (3) the effectiveness of the combination of using rice straw compost and NPK fertilizer on the size of stems and leaves of Ipomoea reptans poir. Two factorial design was applied in this research. The results were obtained: (1) the application of rice straw compost was significantly effective in increasing stem height, leaf length and leaf width but could not increase the rate of increase in the number of  kale land leaves, (2) NPK fertilizer treatment had a real effect on increasing the overall growth parameters observed, (3) ) the combined application of rice straw compost and NPK fertilizer did not have a significant effect on leaf width, number of leaves, leaf length and stem height of  kale land.